Quantification and characterization of interaction between nanoparticles and fines migration: article - Shalah, Shah Rizal; Yahya, Effah; Mohd Shafian, Siti Rohaida (2018)
Nanotechnology has potential in solving and managing several problems in the petroleum industry mainly in Enhanced Oil Recovery (EOR). Nanoparticles technology allows the combination of the high surface area available and the migrateable of formation fines can be fixate by using these particles with the action from the surface of material. In this paper, the experiment of quantification and characterization of interaction between nanoparticles and fines suspension was presented. Thu, the objective of this experiment is to investigate the stability and compatibility of nanoparticles used in reducing fines movement by performing zeta – potential, FESEM – EDX analysis. Another objective is to observe the effect from the migration of fines throughout the pore throat by injecting different types of nanofluid concentration in well formation. The glass beads was used in this experiment as a porous media (synthetic form) to mimic reservoir rocks where fine migration normally occurs. The glass beads are then treated with the different concentration of nanofluids where the bentonite will flow through the treated glass beads. Zeta – potential, FESEM – EDX analysis and adsorption rate were find to determine the most effective nanofluids during this experiment. As a result, MgO with concentration of 1.0% became the most effective nanoparticles that can used to prevent the fines migration because it have higher rate of adsorption.